(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To determine the presence of potential indoor breeding sites, to determine the extent of knowingness about dengue and preventive services provided. Results: Out of 199 respondents, 85.4% knew about Dengue out of which 52.8% regarded it to be a viral disease. Majority had gutter covers among all breeding sites 70.4%. 58.8% had AC and its water leakage and 54.8% had solid waste in the form of tins, shoppers, bottle caps. The commonly used repellant was anti-mosquito spray 39.2% and coils 18.6%. Household cases of Dengue during the last year outbreak were 54.8% and 61.3% in neighborhood. 39.7% respondents were facilitated by the Indoor spraying by the Health team whereas 73.9% had outdoor spraying done by the Health Team. 34.7% respondents reported that recent filling of holes and depressions has been done. The major source of awareness among the respondents is due to Media 94.9%, family and friends 90.9% and doctors 27.6%. Conclusions: Majority of the people have a good knowledge about Dengue and its transmission which can be either due to greater proportion of educated people in the sample or mass media campaigns since last year outbreak. Still many potential breeding sites have been kept in the houses which are not checked.